2022
DOI: 10.1039/d1dt02878b
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Cu(ii) complexation by ATCUN/NTS and related peptides: a gold mine of novel ideas for copper biology

Abstract: The aim of this perspective is to help revive studies of the kinetics of formation and exchange in Cu(ii)–peptide complexes. Such studies have the power to reveal novel reactive intermediates and set timeframes for actual physiological processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 121 publications
1
15
0
Order By: Relevance
“…The formation of Cu(AAH) is at least 20 times slower than that of Cu(AH). To account for this difference, we have to take into consideration very recent reports on the kinetics of formation of ATCUN Cu II complexes [ 81 , 82 , 83 , 84 , 85 , 86 ]. It proceeds via several successive steps: anchoring of the Cu II by the imidazole ring of His, then formation of a metallacycle with the anchoring of the N-terminal amine, leading to the 2N intermediate ( Scheme S2 for a drawing of the various intermediates described in this work) and rearrangement of the 4N ATCUN motif [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…The formation of Cu(AAH) is at least 20 times slower than that of Cu(AH). To account for this difference, we have to take into consideration very recent reports on the kinetics of formation of ATCUN Cu II complexes [ 81 , 82 , 83 , 84 , 85 , 86 ]. It proceeds via several successive steps: anchoring of the Cu II by the imidazole ring of His, then formation of a metallacycle with the anchoring of the N-terminal amine, leading to the 2N intermediate ( Scheme S2 for a drawing of the various intermediates described in this work) and rearrangement of the 4N ATCUN motif [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…This finding is consistent with our previous proposal that the IC to 4N transition rate in GGH, and presumably other ATCUN peptides, is controlled by conformational equilibria in the IC. 1,10 To conclude, in this study we systematically analysed the effect of the 1 st and 2 nd sphere on the rate of formation of cupric 4N ATCUN complexes, first reported for the GGH tripeptide. 10 Data for GGH analogues with respective nitrogen atoms excluded from Cu(II) binding revealed that despite the absence of a chelate effect, the formation of a metastable IC complex with {NH 2 + N Im } coordination is more than a hundred-fold faster than the {NH 2 + N − } or {N − + N Im } alternatives.…”
Section: Dalton Transactions Communicationmentioning
confidence: 99%
“…A knowledge of reaction rates can help clarify such issues in copper physiology, as its cellular uptake or contribution to Alzheimer's disease pathology. 1 In biological processes the Cu( ii ) ions ought to be exchanged between different protein partners within strict timeframes. For instance, the hCTR1 cellular transporter apparently requires just 100 ms to deliver a copper ion to a cell, 2 while Cu( ii ) release and reuptake in the synaptic cleft occur within a few milliseconds.…”
mentioning
confidence: 99%
See 2 more Smart Citations